Diagnosis in industrial processes - Vásquez Capacho, John William (Visión electrónica, 2017)
This article describes the most important aspects in the diagnosis of failures on industrial processes. An analysis of process safety is seen from monitoring tools including expert systems as well as intelligent hybrid models. The article continues to identify aspects such as reliability, risk analysis, fault diagnosis techniques and industrial control and safety systems in processes. Reliability and risk analysis provide important information in a process safety tool; analyzes such as HAZOP, FMEA, Fault trees and Bow tie are described through this article. Then compiled and summarized the different techniques and models of fault diagnosis concluding with a presentation of control and safety systems in an industrial process